2011
DOI: 10.1364/ol.36.002587
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz imaging through self-mixing in a quantum cascade laser

Abstract: Article:Dean, P, Lim, Y, Valavanis, A et al. (10 more authors) (2011) Terahertz imaging through self-mixing in a quantum cascade laser. Optics Letters, 36 (13 We demonstrate terahertz (THz) frequency imaging using a single quantum cascade laser (QCL) device for both generation and sensing of THz radiation. Detection is achieved by utilizing the effect of self-mixing in the THz QCL, and, specifically, by monitoring perturbations to the voltage across the QCL, induced by light reflected from an external object b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 19 publications
0
92
1
Order By: Relevance
“…But, more recently, it has been shown that the emitting QCL cavity itself can be used as a radiation selfdetector, providing system miniaturization, and absorptioncoefficient-sensitive reflection imaging (for a review, see [13]). This Ôself-mixingÕ approach has been highly successful, and it has been possible to demonstrate: displacement sensing interferometry [14]; two-dimensional imaging [15], imaging over distances exceeding 10 m [16]; and, swept frequency coherent imaging, enabling the measurement of porcine tissue [17], inter alia.…”
Section: Thz Qcl Developmentsmentioning
confidence: 99%
“…But, more recently, it has been shown that the emitting QCL cavity itself can be used as a radiation selfdetector, providing system miniaturization, and absorptioncoefficient-sensitive reflection imaging (for a review, see [13]). This Ôself-mixingÕ approach has been highly successful, and it has been possible to demonstrate: displacement sensing interferometry [14]; two-dimensional imaging [15], imaging over distances exceeding 10 m [16]; and, swept frequency coherent imaging, enabling the measurement of porcine tissue [17], inter alia.…”
Section: Thz Qcl Developmentsmentioning
confidence: 99%
“…Of these, monitoring the laser terminal voltage is preferable as it obviates the need for an external terahertz detector. 3 The small voltage variation (referred to as the SM signal) depends on both the amplitude and phase of the electric field of the reflected laser beam. This results in a highly sensitive and compact sensing technique that can probe information about the complex reflectivity or refractive index of the external target.…”
Section: Figure 1 Schematic Diagram Of the Setup For Tissue Imaging mentioning
confidence: 99%
“…21 The total amplitude change of the laser terminal voltage (3 lV peak-to-peak) as the target is displaced is an order of magnitude smaller than the typical signal obtained for in-plane diode lasers or vertical-cavity surface-emmiting lasers (which are both in the tens of microvolts 22,23 ) and several orders smaller than the terminal voltage change observed in terahertz QCLs (millivolts). 19,24 The experimental self-mixing waveform obtained in this way can be modelled through the use of the excess phase equation (that is, the steady-state solution to the Lang-Kobayashi rate equation model for a laser under optical feedback), when the stimulus is simply displacement linear in time. 7,25 The broken line in Fig.…”
mentioning
confidence: 99%
“…As we have demonstrated in earlier work, self-mixing sensors are most sensitive when operated close to the laser threshold. 24 With low threshold currents and low bias voltages (leading to input-power requirements almost two orders of magnitude lower than those for QCLs) ICLs operated in CW at room-temperature are perfectly positioned to become the lasers of choice for MIR SM sensors. Our demonstration paves the way for the application of ICL-based SM systems to the identification or analysis of gases and materials at MIR wavelengths.…”
mentioning
confidence: 99%